(untitled) (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
In 1929, the governor of Algeria, Pierre Bordes, declared that it was necessary to make France become obsessed with Algeria. Since the 1930s, the magazine Algeria seemed to set a similar agenda throughout its three series (1933-1939, 1940-1943, 1948-1962). Algeria was the monthly magazine published by the « Office Algérien d’Action Économique et Touristique » (OFALAC), which was responsible for the commercial promotion of Algeria in France and abroad. Through « propagandistic » advertising, Algeria aimed to build a strong relationship between metropolitan France and the colony. Which strategies did it employ to popularise this « obsession with Algeria »? And what role did this sponsorship play in the broader historical context of WW2 and the independence movement? By analysing both paratextual elements such as covers, reportage images, advertisements, and the texts themselves, I will discuss Algeria’s visual and textual « branding ». Through its iconographic and descriptive bric-a-brac, can Algeria be seen as part of the « touristic invention » of the Mediterranean that follows its « scientific invention » and «literary invention» ?